Differential expression of microRNA-411 and 376c is associated with hypertension in pregnancy - Yang,Hui-li (2019)
Preeclampsia is a major reason of morbidity and mortality in pregnant women and perinatal fetus. Hence, it is of prime importance that diagnostic markers are defined to predict chances of preeclampsia in pregnant women. It has been previously shown that microRNA (miRNA)-376c expression is decreased in the placenta of preeclampsia patients at term. Even though this decrease was not mimicked in the placenta at the pre-term stage, miR-376c expression was decreased in the plasma of these patients as early as the second trimester. Plasma and placenta specimens were obtained from pregnant women having unifetal gestation undergoing perinatal care between January 2014 and December 2016 (n=49). Early trimester placentas were collected from patients undergoing terminated pregnancies through dilation and curettage procedure. Our results showed that in addition to miR-376c, miR-441 levels were decreased in the placenta of preeclampsia patients, and this decrease occurred both at pre-term and at term. This decrease is also mimicked in the plasma levels at both early and late weeks of pregnancy, highlighting that miR-441 levels can serve as a diagnostic marker of risk of preeclampsia in pregnant women. Overexpression of the miR-441, as well as miR-376c, promoted cell viability, migration, and invasion in the human immortalized cytotrophoblast cell line HTR8/SVneo, indicating that their decrease in pregnant women would result in anomalous apoptosis and functional imbalance resulting in premature abortion and other complications. MiR-441 level can thus potentially serve as diagnostic marker of preeclampsia in pregnant women.